How (specific) would you like your T-cells today? Generating T-cell therapeutic function through TCR-gene transfer - Daniel-Meshulam, Inbal; Ya'acobi, Shlomo; Ankri, Chen; Cohen, Cyrille J. (Frontiers in Immunology, 2012)
T-cells are central players in the immune response against both pathogens and cancer. Their specificity is solely dictated by the T-cell receptor (TCR) they clonally express. As such, the genetic modification of T lymphocytes using pathogen- or cancer-specific T-cell receptors represents an appealing strategy to generate a desired immune response from peripheral blood lymphocytes. Moreover, notable objective clinical responses were observed in terminally-ill cancer patients treated with TCR-gene modified cells in several clinical trials conducted recently. Nevertheless, several key aspects of this approach are the object of intensive research aimed at improving the reliability and efficacy of this strategy. Herein, we will survey recent studies in the field of TCR-gene transfer dealing with the improvement of this approach and its application for the treatment of malignant, autoimmune and infectious diseases.